13.6k views
1 vote
-2m^3 n^2 to the power of 4

User Shekwi
by
6.0k points

1 Answer

6 votes

Answer:


16m^(12)n^(8)

Explanation:

The rule of exponents for powers of powers applies.


(a^b)^c=a^(b\cdot c)\qquad\text{the applicable rule}\\\\(-2m^(3)n^(2))^(4)=(-2)^(4)m^(3\cdot 4)n^(2\cdot 4)\\\\=16m^(12)n^(8)

_____

The rules of exponents are not hard to remember if you recall that an exponent signifies repeated multiplication. That is ...

... a^3 = a·a·a . . . . . . the factor a appears 3 times in the product

so (a^3)^2 = (a·a·a)·(a·a·a) = a^(3·2) = a^6

User Dmitry Romanov
by
5.6k points